Shadows in death - Robb, J. D., 1950- (2020)
"Lt. Eve Dallas is about to walk into the shadows of her husband's dangerous past."--
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Detective and mystery fiction; Thrillers (Fiction)